2018
DOI: 10.1021/acsami.7b19834
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of “Waste Plastic” into Photocatalytic Nanofoams for Environmental Remediation

Abstract: Plastic debris is a major environmental concern, and to find effective ways to reuse polystyrene (PS) presents major challenges. Here, it is demonstrated that polystyrene foams impregnated with SnO are easily generated from plastic debris and can be applied to photocatalytic degradation of dyes. SnO nanoparticles were synthesized by a polymeric precursor method, yielding specific surface areas of 15 m/g after heat treatment to 700 °C. Crystallinity, size, and shape of the SnO particles were assessed by X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…However, CO 2 is produced as a by-product in this study and the conversion efficiency is low. After that, although there are some reports about the photocatalytic treatment of plastic, nearly all of them are focused on degradation (Feng et al, 2011;de Assis et al, 2018;Das and Mahalingam, 2019). No typical study about the photocatalytic H 2 production from plastic waste has been reported.…”
Section: Photocatalytic Plastic Upgrading To Fine Chemicals Integrated With H 2 Productionmentioning
confidence: 99%
“…However, CO 2 is produced as a by-product in this study and the conversion efficiency is low. After that, although there are some reports about the photocatalytic treatment of plastic, nearly all of them are focused on degradation (Feng et al, 2011;de Assis et al, 2018;Das and Mahalingam, 2019). No typical study about the photocatalytic H 2 production from plastic waste has been reported.…”
Section: Photocatalytic Plastic Upgrading To Fine Chemicals Integrated With H 2 Productionmentioning
confidence: 99%
“…[ 175 ] On the other hand, Assis et al demonstrated photocatalytic NCM nanofoams derived from polystyrene (PS) waste and SnO 2 for the degradation of dyes. [ 176 ] SnO 2 nanoparticles incorporated NCM nanofoams showed the increased specific surface area (48 m 2 g −1 ) compared to the pristine SnO 2 (15 m 2 g −1 ) with higher photodegradation efficiency and kinetics of RhB under UV irradiation (degradation rate of ≈98%, 0.054 min −1 ) compared to the SnO 2 nanoparticles (94%, 0.037 min −1 ) and the PS foam (25%). The NCM/SnO 2 nanofoams retained the photocatalytic activity for up to four cycles, further demonstrating the feasibility of recycling the polymeric waste to fabricate new materials.…”
Section: Functionalized Nanoporous Carbons (F‐ncm) and Their Potentiamentioning
confidence: 99%
“…These findings reveal that NCM is good support for the photocatalysts that can significantly enhance the photocatalytic activity for the degradation of dyes and water splitting after the hybridization. [ 175–176 ]…”
Section: Functionalized Nanoporous Carbons (F‐ncm) and Their Potentiamentioning
confidence: 99%
“…A bulk material rather than a powder is preferred for many material applications especially when used as a support or matrix, since it takes full advantage of the mechanical stability and easy reuse [1]. Polystyrene (PS) is a common polymer and has been widely used in many fields, such as plastic products, insulation materials, catalyst supports, chromatographic separation, gas or oil absorption [2][3][4][5][6][7][8]. Like many thermoplastics, extrusion, compression or injection molding is usually used for shaping PS in industry, but many attempts have been made to produce a functional polymeric monolith without complex shaping equipment and high energy consumption.…”
Section: Introductionmentioning
confidence: 99%